2014
DOI: 10.4103/0971-6203.139003
|View full text |Cite
|
Sign up to set email alerts
|

A dosimetric evaluation of flattening filter-free volumetric modulated arc therapy in nasopharyngeal carcinoma

Abstract: Purpose:To explore the dosimetric effects of flattening filter-free (FFF) beams in volumetric modulated arc therapy (VMAT) of nasopharyngeal carcinoma via a retrospective planning study.Materials and Methods:A linear accelerator (LINAC) was prepared to operate in FFF mode and the beam data were collected and used to build a model in TPS. For 10 nasopharyngeal carcinoma (NPC) cases, VMAT plans of FFF beams and normal flattened (FF) beams were designed. Differences of plan quality and delivery efficiency between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…This was in line with the several previous studies in which reduction of TT of 20–50% have been reported 17,20,21. Because of this advantage, the use of FFF beams has been extended to VMAT treatment of nasopharynx22 and prostate23 cancers. Nevertheless, despite the FFF beam technology demonstrated attractive practical advantages over the conventional beam IMRT, the understanding of the biological effect of such a high dose rate treatment on body tissues which may have consequence on late toxicities is still not certain and needs to be proven by longer term clinical studies.…”
Section: Discussionsupporting
confidence: 88%
“…This was in line with the several previous studies in which reduction of TT of 20–50% have been reported 17,20,21. Because of this advantage, the use of FFF beams has been extended to VMAT treatment of nasopharynx22 and prostate23 cancers. Nevertheless, despite the FFF beam technology demonstrated attractive practical advantages over the conventional beam IMRT, the understanding of the biological effect of such a high dose rate treatment on body tissues which may have consequence on late toxicities is still not certain and needs to be proven by longer term clinical studies.…”
Section: Discussionsupporting
confidence: 88%
“…Many factors can affect the application of VMAT in patients with NPC, including the large planning target volume (PTV), the proximity of vital normal tissues, which make the planning of radiation treatment of NPC cases challenging [24]. Therefore, the aims of the present study were present study were to investigate the therapeutic role of the flattening filter-free (FFF) mode in volumetric modulated arc therapy (VMAT) compared with the flattening filter (FF) mode in patients with locally advanced nasopharyngeal carcinoma (NPC).…”
Section: Introductionmentioning
confidence: 99%